Scintillation and optical properties of polycrystalline p-terphenyl - Gorbacheva, T.E.; Galunov, N.Z.; Panikarskaya, V.D.; Lazarev, I.V. (Functional Materials, 2013)
The work is devoted to study of scintillation and optical properties of polycrystalline p-terphenyl obtained by hot pressing of powders of different dispersion. The influence of grain size of the powders on the light output and optical transparency of the polycrystalline samples was studied. It was shown that the grain size in the range of 2.2–3 mm is optimal for registration of short-range radiation at the selected sample thickness. Using such grain size it is possible to get the light output of the polycrystalline scintillator of about 50–75 % relatively to one of the single crystal. It was also shown that low optical transparency is the major factor deteriorating the scintillation characteristics of the samples with relatively small grains.